2015
DOI: 10.1136/archdischild-2014-307656
|View full text |Cite
|
Sign up to set email alerts
|

The use of laboratory biomarkers for surveillance, diagnosis and prediction of clinical outcomes in neonatal sepsis and necrotising enterocolitis 

Abstract: Biomarkers have been used to differentiate systemic neonatal infection and necrotising enterocolitis (NEC) from other non-infective neonatal conditions that share similar clinical features. With increasing understanding in biochemical characteristics of different categories of biomarkers, a specific mediator or a panel of mediators have been used in different aspects of clinical management in neonatal sepsis/NEC. This review focuses on how these biomarkers can be used in real-life clinical settings for daily s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 32 publications
0
60
0
5
Order By: Relevance
“…For many years, researchers have sought plasma, urine or stool biomarkers that would be diagnostic for NEC [13]. One of these biomarkers is intestinal fatty acid binding protein (I-FABP), which is released into the circulation from damaged enterocytes and is excreted in urine.…”
Section: Improved Diagnostic Methodsmentioning
confidence: 99%
“…For many years, researchers have sought plasma, urine or stool biomarkers that would be diagnostic for NEC [13]. One of these biomarkers is intestinal fatty acid binding protein (I-FABP), which is released into the circulation from damaged enterocytes and is excreted in urine.…”
Section: Improved Diagnostic Methodsmentioning
confidence: 99%
“…144,199,203 The potential of biomarkers to distinguish serious NEC, that may require surgery, from milder disease, is being explored. 205 Blakely reported that, in 156 infants undergoing laparotomy or drainage for NEC or SIP, the indication was PP in 64%, clinical deterioration despite medical therapy in 66%, PVG in 14%, abdominal wall erythema in 28%, infected ascites in 5%, and other factors in 26%. 33 Obviously one individual could have more than one indication.…”
Section: Treatmentmentioning
confidence: 99%
“…The introduction of new methods for monitoring, such as biomarkers and NIRS, 203,205 may influence the role of imaging in this context. Although most survey respondents thought that US would, at least sometimes, be useful, the often repeated objections of availability and operator dependency 211 were expressed, as were concerns about the validity of ultrasonographic findings.…”
Section: ❖ Imaging Routinesmentioning
confidence: 99%
“…The clinical properties and laboratory characteristics of such biomarkers, e.g. for neonatal sepsis, have been summarised in “box 1” under the heading of “ideal biomarker” in a previous review [8]. In contrast to surveillance studies, the diagnostic test is usually performed at the first suspicion of an illness in symptomatic subjects.…”
Section: Designing a Diagnostic Study And Biomarker Discoverymentioning
confidence: 99%
“…For practical purposes, tests associated with diagnostic accuracy, in general, may be classified into three broad categories in neonatology: (i) screening or surveillance of a disease, (ii) “early” diagnosis and (iii) predicting the severity and prognosis at clinical presentation [8, 9]. …”
Section: Designing a Diagnostic Study And Biomarker Discoverymentioning
confidence: 99%